Effects of sedimentation, microgravity, hydrodynamic mixing and air–water interface on α-synuclein amyloid formation. Issue 14 (17th March 2020) - Zhou, Jiangtao; Ruggeri, Francesco S.; Zimmermann, Manuela R.; Meisl, Georg; Longo, Giovanni; Sekatskii, Sergey K.; Knowles, Tuomas P. J.; Dietler, Giovanni
Abstract : A comprehensive analysis on the impact of sedimentation, microgravity hydrodynamic mixing and air–water interface on α-synuclein aggregation kinetics. Abstract : The formation of amyloid fibrils is a characterizing feature of a range of protein misfolding diseases, including Parkinson's disease. The propensity of native proteins to form such amyloid fibril, both in vitro and in vivo, is highly sensitive to the surrounding environment, which can alter the aggregation kinetics and fibrillization mechanisms. Here, we investigate systematically the influence of several representative environmental stimuli on α-synuclein aggregation, including hydrodynamic mixing, the presence of an air–water interface and sedimentation. Our results show that hydrodynamic mixing and interfacial effects are critical in promoting several microscopic steps of α-synuclein aggregation and amyloid fibril formation. The presence of an air–water interface under agitation significantly promoted primary nucleation. Secondary processes were facilitated by hydrodynamic mixing, produced by 3D rotation and shaking either in the presence or in the absence of an air–water interface. Effects of sedimentation, as investigated in a microgravity incubator, of α-synuclein lead only to minor changes on the aggregation kinetics rates in comparison to static conditions. These results forward the understanding of α-synuclein fibrillization, paving the way for the development of high-throughput assays for the screening of pharmacological approaches targeting Parkinson's disease.